A comparative study of the resurfacing effect of microdermabrasion versus glycolic acid peel in the management of acne scars - Rathi vanthitha, Pallavi; Ganga vellaisamy, Seethalakshmi; Gopalan, kannan; Govindarajan, Nanjappachetty (Journal of Pakistan Association of Dermatologists, 2018)
Objective To compare the resurfacing effect of microdermabrasion versus glycolic acid peeling in the treatment of acne scars. Â Methods A total of 80 patients were selected randomly and divided into two groups A (treated with microdermabrasion) and B (treated withÂ Â glycolic acid peeling). Data were coded and analyzed. Â Results Of the 80 participants, 56 completed all 6 sessions. Among those 56 patients, 24 patients belonged to group A and 32 patients belonged to group B. In group A, good improvement was noted in 16.7% of the patients, 67% showed fair improvement, 12.5% showed poor improvementÂ and 4.2% had no change after 6 sessions. In group B, 3% of the patients showed excellent improvement, 3% showed good improvement, 81.3%Â showed fair improvement, 6.25%Â showed poor improvement and no change was noted in 6.25% of the patients. Â Conclusion This study infers that superficial scars showed greater improvement with microdermabrasion while reduction in active acne lesions was much more with glycolic acid peel. However, no statistically significant differences were found between the outcomes of both therapeutic modalities. Â